The Influence of Digital Literacy, Innovation, and Creativity on the Performance of Digital Entrepreneurs in the Creative Economy Sector - Cruz, Leonel da (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the influence of digital literacy, innovation, and creativity on the performance of digital entrepreneurs in the creative economy sector. The approach used was quantitative with a survey method of digital-based creative economy business actors. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results of the study indicate that digital literacy, innovation, and creativity have a positive and significant effect, both partially and simultaneously, on the performance of digital entrepreneurs. Digital literacy plays a role in improving the ability of business actors to utilize technology to expand markets and improve operational efficiency. Innovation drives the creation of added value through product and service development, while creativity strengthens competitiveness through differentiation and attractive promotional strategies. These findings confirm that strengthening the capacity of digital literacy, innovation, and creativity is a strategic factor in improving the performance and sustainability of businesses in the creative economy sector, especially in facing the increasingly competitive dynamics of the digital economy.